2019
DOI: 10.1177/1087054719886353
|View full text |Cite
|
Sign up to set email alerts
|

Advertising Influences Food Choices of University Students With ADHD

Abstract: Objective: Previous research in adults with ADHD showed high rates of obesity and unhealthy food choices. There is evidence that contextual cues, for example, advertisements, influence food choices. This study assessed the sensitivity of university students with ADHD to advertised food. Method: University students ( N = 457) with and without ADHD participated in a cafeteria field experiment. Food choices were examined in periods of advertising either healthy or unhealthy sandwiches. Results: Students with ADHD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…To illustrate, recent research findings on adulthood ADHD can also be applied to children. Hershko et al (2019Hershko et al ( , 2020 alarmed the attractiveness and convenience of food items can exacerbate obesity issues in the clinical population with more responsiveness to advertisement and resultant unhealthy food choices than non-ADHD groups. With the present findings at this stage, the four lifestyle factors can be monitored in children with ADHD to arrange maximized intervention effects with the supported mediation model in mind while the measurement issues that are discussed above posit caution in interpreting and applying the current findings.…”
Section: Discussionmentioning
confidence: 99%
“…To illustrate, recent research findings on adulthood ADHD can also be applied to children. Hershko et al (2019Hershko et al ( , 2020 alarmed the attractiveness and convenience of food items can exacerbate obesity issues in the clinical population with more responsiveness to advertisement and resultant unhealthy food choices than non-ADHD groups. With the present findings at this stage, the four lifestyle factors can be monitored in children with ADHD to arrange maximized intervention effects with the supported mediation model in mind while the measurement issues that are discussed above posit caution in interpreting and applying the current findings.…”
Section: Discussionmentioning
confidence: 99%
“…4.1.1 Self-health condition. Hershko et al (2021) found that individuals with ADHD consume more unhealthy food (compared to those without ADHD) when they are exposed to Scholars have also observed that the body weight of an individual is associated with the impact of advertising on unhealthy food consumption. For instance, Andreyeva et al (2011) reported a stronger association for individuals with high BMI (a measure commonly used for obesity or body fat that is calculated with an individual's weight and height) between unhealthy food advertising and increased consumption of unhealthy food items.…”
Section: Viewer Attributesmentioning
confidence: 96%
“…The third assumption is that individual dispositional factors determine susceptibility to food cues in advertisements [21]. Evidence clearly shows that food advertising affects eating behavior [6], but stronger effects have been found for individuals with a higher weight status [29], more impulsive individuals [30,31], restrained eaters [32], or children who are prohibited to consume candies [33•]. The REFCAM has shown to be adequate to describe, understand, and predict the effects of food cues in advertising on the intake of palatable snacks [6].…”
Section: The Underlying Mechanism Of Unhealthy Food Marketingmentioning
confidence: 99%